Constitutional rights and freedoms of national minorities: The Experience of Serbia - Polovchenko, Konstantin A. (Opción, 2019)
The method of case study allowed a comprehensive review of the institution for the protection of the rights of national minorities in the system of constitutional rights and freedoms in Serbia. As a result, more than a third of the constitutional text is devoted to the regulation of the institution for the protection of rights and freedoms. The author concluded that the Republic of Serbia has created a reliable mechanism for protecting the national minorities’ rights meeting the highest international standards; the Serbian legal system ensures sustainable development of its citizens